El procedimiento abreviado en la legislación penal Ecuatoriana - Macías Rodríguez, Ángel Rodolfo (2017)
This research work entitled "THE CRIMINAL PROCEDURE LAW SHORTCUTS IN ECUADOR", is to study the current figure of summary proceedings since August 2014 in the framework of the Ecuadorian Criminal Law. Its preparation was counted with an extensive bibliography on Administration of criminal justice, from doctrinal concepts, legal nature, historical development and a comprehensive analytical and critical study of the rules of the Constitution of the Republic of Ecuador, the Organic Code Integral Criminal , the Universal Declaration of Human rights, which is vital to the effective realization of the fundamental rights of society in general, likewise strives to conducting field research comprising conducting surveys and interviews Counsel in free practice, prosecutors; and the judges of criminal guarantees of the city of Quito, because it is legal reforms, culminating in the drafting of the conclusions and recommendations, as well as the proposed legal reform. National Assembly to promote urgent Draft amendments to the Criminal Code of Integral, with the aim of providing greater legal certainty for those convicted. The state through its competent bodies promotes true respect for constitutional guarantees in regard to due process and thus fairer for both offended and for processed processes is applied. The end of the criminal proceedings is not only to find the material truth, but proceed in accordance with the principles that characterize a criminal trial as the right to a rule of law so that it is obliged not only the judge but fiscal, mentoring both the rights of the victim and the offender. Special procedures must not violate the guarantees of due process that seeks to protect the system, so that should be taken into account for application of summary procedure recidivism processing That should amend Article 635 of the Code of Criminal Integral because for application of summary procedure is not taken into account the